In situ Investigation of Microwave Impacts on Ethylene Glycol Aqueous Solutions - Asakuma, Y.; Matsumura, S.; Asada, M.; Phan, Chi (2018)
Recently, the in-situ IMPACT of MICROWAVES on the behavior of aqueous solutions have been reported. The results, including surface tension and in situ bubble formation, indicated a nonthermal effect of microwave on solutions. To clarify the role of fluid properties on such effects, this study applied microwave to ethylene glycol (EG) aqueous solutions at different concentrations. The surface tension, bubble size and convection were monitored during and after microwave irradiation. It was found that surface tension reduction was maximized in the medium EG content, 20 to 60 vol.%. The size of bubble formed during microwave was reduced by the addition of EG. The convection was also reduced by EG. The obtained data indicated that the dielectric constant and intermolecular bonds were the main underlining principles for microwave effects. The new insights can be used to provide practical ways to manipulate microwave effects on aqueous solutions.